2007
DOI: 10.1007/s00406-007-0719-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of engagement in the Alcoholics Anonymous group or to psychotherapy among Brazilian alcoholics

Abstract: The identification of predictors of engagement is important to guide clinicians in the choice of the treatment strategies that are more likely to be successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…One study reported no demographic differences between those who attend AA and those who do not (Humphreys, Mavis, & Stofflemayr, 1994). Other studies found that certain demographic groups, such as women (Humphreys, Mavis, and Stofflemayr, 1991), those with higher levels of education (Terra et al, 2007), and African Americans (Humphreys et al, 1991; Kelly & Moos, 2003) are more likely to attend or less likely to drop out of AA. Higher substance use severity and more family, social and psychological problems have been shown to be associated with later AA participation (Emrick, Tonigan, Motgomery, & Little, 1993; Humphreys et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported no demographic differences between those who attend AA and those who do not (Humphreys, Mavis, & Stofflemayr, 1994). Other studies found that certain demographic groups, such as women (Humphreys, Mavis, and Stofflemayr, 1991), those with higher levels of education (Terra et al, 2007), and African Americans (Humphreys et al, 1991; Kelly & Moos, 2003) are more likely to attend or less likely to drop out of AA. Higher substance use severity and more family, social and psychological problems have been shown to be associated with later AA participation (Emrick, Tonigan, Motgomery, & Little, 1993; Humphreys et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000 the concept of engagement has been examined in several studies in the fi eld of groupwork. A number of researchers have assessed the engagement of group members on the basis of their attendance at meetings (Comfort et al, 2000;Daly et al, 2001;Fiorentine et al, 1999a;Prado et al, 2006;Terra et al, 2007). Considering attendance alone as an indicator of engagement is a major limitation.…”
Section: Engagement As a Conceptmentioning
confidence: 99%
“…Daly et al (2001) hypothesized that the unemployed had more trouble keeping a regular schedule. People with mental health problems seem to be less engaged and more likely to drop out (Amodeo et al, 2008;Graff et al, 2008, Terra et al, 2007. Engaged individuals, on the other hand, generally have a higher level of education (Daly et al, 2001;Terra et al, 2007).…”
Section: Ontosystem Factors: Participantsmentioning
confidence: 99%
“…Thus, a determination of more specific aspects of AA is highly important to better understand the reasons for adherence or nonadherence. The influence of co‐morbid conditions and demographic characteristics on adherence to AA groups has been previously documented 20 …”
Section: Introductionmentioning
confidence: 99%